Isolated Tuberculous Peroneal Tenosynovitis: A Case Report - Ajoy, S.M (J Clin Diagn Res, 2015)
Tuberculosis (TB) of osteoarticular sites constitutes less than 3% of total patients with tuberculosis. Involvement of the foot and ankle is less than 0.3% of total disease. Even in a country like India, where the incidence of TB is not uncommon, we do not encounter isolated tenosynovitis. We present a young man with bilateral tubercular peroneal tenosynovitis who was evaluated with relevant investigations and operated upon and started on antitubercular treatment (ATT) in consultation with the pulmonologist. After tenosynovectomy and commencement of ATT, the patient’s symptoms improved.